Linear nevus sebaceous syndrome with bilateral ocular involvement in a Bangladeshi child: A case report with literature review - Roy, Soma Rani; Biswas, Sujit Kumar; Hoque, Fahmida; Kader, Md. Sazzad (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2023)
The linear sebaceous nevus is one of a variety of epidermal nevi, which is a congenital ectodermal hamartoma that occurs due to post-zygotic mosaic mutation. Such sebaceous nevus is one of the commonest nevi, and up to 30% are associated with syndromic associations, which are rare. After cutaneous manifestation, central nervous system and ocular anomalies are common and found in almost every case. Multiorgan involvement can lead to various minor or major morbidities. Adequate knowledge and a high degree of suspicion can identify this rare disease and can minimize unwanted morbidity.